2021
DOI: 10.1088/1755-1315/722/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feeding different levels of dandelion leaf powder (Taraxacum officinale) in the diet on the productive and physiological performance of broiler chickens, strain Ross-308.

Abstract: This study aimed to know the effect of feeding different levels of dandelion leaf powder on the productive and some physiological traits of broiler chickens, in which 180 one-day age chicks of the unsexed Ross 308 strain were used. The chicks were distributed randomly into 4 treatments that included each treatment (3 replicates at an average of 15 chicks for each replicate). The transactions were divided into The first (control) treatment was without addition, the second, third and fourth treatments included t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Asteraceae plants have already been studied due to their abundant bioactive substances, which are conducive to improve the performance of poultry [11][12][13]. Previous results revealed that dietary supplementation with 1 g/ kg dandelion leaf powder increased the total weight gain for 1-21 day and 1-35 day, and decreased the cumulative feed conversion factor for 1-21 day [14]. Yan et al (2012) [15] found that dietary inclusion with 1 g/kg dandelion increased the ADG and the G:F ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Asteraceae plants have already been studied due to their abundant bioactive substances, which are conducive to improve the performance of poultry [11][12][13]. Previous results revealed that dietary supplementation with 1 g/ kg dandelion leaf powder increased the total weight gain for 1-21 day and 1-35 day, and decreased the cumulative feed conversion factor for 1-21 day [14]. Yan et al (2012) [15] found that dietary inclusion with 1 g/kg dandelion increased the ADG and the G:F ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, higher TP levels may indicate less damage to the intestinal mucosa from infection, leading to better nutrient absorption or reduced leakage into the intestinal lumen. Previous studies on chickens have demonstrated that dandelion reduces the concentrations of TG, TC, and GLU in the blood of uninfected chickens [ 24 , 26 ]. However, such hypoglycemic and hypocholesterolemic effects at 5 d PI were not observed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Among its antioxidant and anti-inflammatory phenolic compounds, derivatives of hydroxycinnamic acid—specifically chicoric acid, chlorogenic acid, and caffeic acid—have been found in the highest concentrations [ 22 , 23 ]. Various studies have reported dandelions’ ability to improve growth performance in poultry [ 21 , 24 , 25 , 26 ]. A recent study demonstrated that dandelion enhances feed efficiency in broilers by enhancing intestinal barrier function, decreasing proinflammatory cytokines, and optimizing the composition of the intestinal microbiota [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary supplementation with dandelion enhanced the growth performance of pigs [ 13 ] and olden pompano Trachinotus ovatus [ 14 , 15 ]. Noor et al (2021) reported that dietary supplementation of 2.0 g/kg dandelion leaf powder decreased the feed consumption and feed conversion factor of broiler chickens [ 17 ]. In consistent with previous studies, the present study showed that adding dandelion to the diet decreased ADFI and F/G ratio of broilers, and that dandelion supplementation at low dosage in particular, improved broiler performance more than high dosage and CTC.…”
Section: Discussionmentioning
confidence: 99%